Morphological and conceptual influences on the real-time comprehension of optional plural marked sentences in Yucatec Maya - Butler, Lindsay K. (Frontiers in Psychology, 2023)
This psycholinguistic experiment investigated the role of conceptual and morphological number in sentence comprehension with speakers of Yucatec Maya, an indigenous language of Mexico. In a previous picture description experiment with speakers of Yucatec Maya, conceptual number was found to be a significant predictor of the use of optional plural morphology. To replicate the findings in the domain of sentence comprehension, the same picture stimuli were matched with auditorily presented sentences to investigate the effects of conceptual and morphological number on acceptability, accuracy and decision time. Yucatec Maya can address how the effects of conceptual number on sentence processing relate to language specific factors, such as the inflectional richness of a language, since it is an optional plural language and previous work has almost exclusively focused on languages with rich inflectional paradigms. Results showing significant effects of conceptual number in production and interactions of conceptual and morphological number in comprehension suggest that low morphological richness is associated with high conceptual influence in Yucatec Maya.